2009
DOI: 10.1152/ajpheart.00732.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme, a mediator of sepsis that intrinsically generates hydrogen peroxide to cause cardiovascular dysfunction

Abstract: In septic shock, cardiovascular collapse is caused by the release of inflammatory mediators. We previously found that lysozyme (Lzm-S), released from leukocytes, contributed to the myocardial depression and arterial vasodilation that develop in canine models of septic shock. To cause vasodilation, Lzm-S generates hydrogen peroxide (H(2)O(2)) that activates the smooth muscle soluble guanylate cyclase (sGC) pathway, although the mechanism of H(2)O(2) generation is not known. To cause myocardial depression, Lzm-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 41 publications
1
25
1
Order By: Relevance
“…Wentworth and colleagues (29 -31) recently demonstrated that proteins can intrinsically generate H 2 O 2 from singlet oxygen ( 1 O 2 *). Based on the investigations of Wentworth and colleagues, we were able to show that Lzm-S was capable of intrinsically generating H 2 O 2 in this manner (20). Furthermore, we found that this generation of H 2 O 2 by Lzm-S led to activation of pathways that resulted in vasodilation and myocardial depression in ventricular trabecular and carotid artery preparations, respectively (20,23).…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Wentworth and colleagues (29 -31) recently demonstrated that proteins can intrinsically generate H 2 O 2 from singlet oxygen ( 1 O 2 *). Based on the investigations of Wentworth and colleagues, we were able to show that Lzm-S was capable of intrinsically generating H 2 O 2 in this manner (20). Furthermore, we found that this generation of H 2 O 2 by Lzm-S led to activation of pathways that resulted in vasodilation and myocardial depression in ventricular trabecular and carotid artery preparations, respectively (20,23).…”
mentioning
confidence: 79%
“…We previously delineated the pathways by which Lzm-S could cause cardiovascular dysfunction in this condition. In organ bath preparations, we found that these pathways were ultimately dependent on hydrogen peroxide (H 2 O 2 ) signaling (20,23). Although H 2 O 2 is a well-described reactive oxygen species that is known for its cytotoxic effects associated with tissue injury, H 2 O 2 has recently been established as an important signaling molecule, as well (6).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As well as directly degrading bacterial walls, lysozyme has also been reported to be involved in promotion of sepsis and toxic shock by generating hydrogen peroxide, which acts on muscle tissue activating the guanylate cyclase pathway, in turn resulting in vasodilation, and finally leading to cardiovascular collapse (Mink et al, 2009). A second mechanism of action determined lysozyme could also act directly on smooth muscle tissue, with the same end result (Gotes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%